2015
DOI: 10.1039/c5cp02934a
|View full text |Cite
|
Sign up to set email alerts
|

Band tail-induced photoluminescence broadening in heavily In-doped n-type ZnO nanowires

Abstract: We have demonstrated that photoluminescence (PL) is a non-damaging and powerful tool for the characterization of heavily-doped semiconductor nanostructures such as n-ZnO nanowires. The PL shows a redshift and a Gaussian-shaped low-energy wing, indicating a broadening mechanism governed by the impurity band. The electron concentration can be estimated from the PL linewidth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 36 publications
3
10
1
Order By: Relevance
“…Commonly, the activation of describes the non-radiative recombination at low temperature while describes the non-radiative recombination at high temperature. The trend of fitted values are similar with previous reported ZnO nanowires [42]. Fang et al [28] reported the temperature dependence PL of Al-coated ZnO nanostructures and their result showed that the fitting parameters of were 4.1 and 26.5 meV, respectively.…”
Section: Wheresupporting
confidence: 87%
See 1 more Smart Citation
“…Commonly, the activation of describes the non-radiative recombination at low temperature while describes the non-radiative recombination at high temperature. The trend of fitted values are similar with previous reported ZnO nanowires [42]. Fang et al [28] reported the temperature dependence PL of Al-coated ZnO nanostructures and their result showed that the fitting parameters of were 4.1 and 26.5 meV, respectively.…”
Section: Wheresupporting
confidence: 87%
“…It can be observed that the PL intensity increases rapidly first and then smoothly with temperature increasing. The dependence of PL intensity on temperature can be described by the well-known Arrhenius expression [42]:…”
Section: Wherementioning
confidence: 99%
“…Given both optical properties (the red shi of PL spectra and bandgap broadening) and UPS data, the EB-ZnO samples seem to be heavily n-type doped ZnO. Although N-doped ZnO with N-Zn bonds is known as p-type, in our study, n-type doping of EB-ZnO can be explained by (1) the zinc interstitial and oxygen vacancy as the donor result in band tails, which merge with the CB and cause band broadening, 23 or (2) N-C bonds, such as amine groups, Fig. 4 (a adsorbed on the surface can inuence the reduction of W.F due to the interfacial dipole, similarly to the previously reported result.…”
Section: Electronic Propertiesmentioning
confidence: 52%
“…since electrons ll up all the states below E f , the optical band gap increases. 22,23 In addition, for the characterization of EB-ZnO defects, the photoluminescence (PL) spectra of samples are shown in Fig. 3c.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Low-energy tail in PL spectra has been generally observed in semiconductor systems such as III-V semiconductor alloys 29,30,35 , doped semiconductors 36 , carbon nanotubes 37 , and ionic/polar solids [38][39][40] . And several mechanisms have been proposed such as extrinsic structure/impurity traps 36,41 , potential fluctuations 29,30,35 , phonon replica broadening 40 , Fermi-edge singularity effect 37 , and Urbach exciton emission 38,39,42 . Previous studies on 2D lead halide perovskites also have shown asymmetric PL line shape and attributed to extrinsic below gap trap states at surfaces/ interfaces 33,43 .…”
Section: Discussionmentioning
confidence: 99%